Energy efficiency in industry: EU and national policies in Italy and the UK. (1st April 2019) - Malinauskaite, J.; Jouhara, H.; Ahmad, L.; Milani, M.; Montorsi, L.; Venturelli, M.
Abstract: Energy efficiency, which is one of the pillars of the EU's Energy Union strategy, has been proposed as a solution, namely as a highly effective pathway to improve economic competitiveness and sustainability of the European economy, lower emissions, reduce energy dependency and increase security of supply, and job creation. The paper reviews the EU strategies and policies on energy efficiency and argues that further focus should be placed on industrial energy efficiency. Despite a decline in energy consumption in recent years in industry, this sector is one of the largest users of energy in the EU. Therefore, the paper reviews the extent to which the European and national policies in the selected jurisdictions, such as Italy and the UK address energy efficiency in industry and whether there are any measures in place to promote it. Highlights: Legal certainty is required in industrial energy efficiency policies. White Certificates play a major role in industrial energy efficiency in Italy. Yet, constant changes in the WC regulations can act as an investment barrier. The UK's Energy Efficiency policy is underpinned with decarbonisation of the industry.